Ex situ n+ doping of GeSn alloys via non-equilibrium processing. (8th May 2018) - Prucnal, S; Berencén, Y; Wang, M; Rebohle, L; Böttger, R; Fischer, I A; Augel, L; Oehme, M; Schulze, J; Voelskow, M; Helm, M; Skorupa, W; et al.
Abstract: Full integration of Ge-based alloys like GeSn with complementary-metal-oxide-semiconductor technology would require the fabrication of p- and n-type doped regions for both planar and tri-dimensional device architectures which is challenging using in situ doping techniques. In this work, we report on the influence of ex situ doping on the structural, electrical and optical properties of GeSn alloys. n-type doping is realized by P implantation into GeSn alloy layers grown by molecular beam epitaxy (MBE) followed by flash lamp annealing. We show that effective carrier concentration of up to 1 × 10 19 cm −3 can be achieved without affecting the Sn distribution. Sn segregation at the surface accompanied with an Sn diffusion towards the crystalline/amorphous GeSn interface is found at P fluences higher than 3 × 10 15 cm −2 and electron concentration of about 4 × 10 19 cm −3 . The optical and structural properties of ion-implanted GeSn layers are comparable with the in situ doped MBE grown layers.